Cellular and humoral immune response in BALB/c mice against infection with secondary hydatid disease by the lipopolysaccharide extracted from Klebsiella pneumonia. - Asmaa Abdulaziz Ali; Ibrahim Faris Ali (مجلة التربية والعلم, 2010)
ABSTRACT The study investigated the effect of the lipopolysaccharide, (LPS) extracted from Klebsiella pneumoniae, on immune response of BALB/c mice infected with secondary hydatid disease caused by Echinococcus granulosus protoscoleces. The immunopathological changes accompanied with secondary hydatid disease in mice treated with LPS were followed in comparison with the positive control group (mice infected with hydatid disease but not treated with LPS before infection) along 5-3 months period of the experiments. Criteria taken into consideration included the specific cellular immune response, expressed by the change in the delayed-type hypersensitivity (footpad thickness) and humoral immune response expressed by antibody titer, were also considered. Results of the present study revealed an increase in the specific cellular and humoral immune response, expressed by an increase in the delayed type hypersensitivity (footpad thickness) and the titer of the antibody, respectively, in treated mice. Therefore, it may be concluded that the lipopolysaccharide extracted from Klebsiella pneumoniae may possess some stimulating effect on both specific cellular and humoral immune response against infection with hydatid disease.